(Nk(B200-(NlETI@ SO DNQ ROVDENIQs (NMATERIALY NAU^(B.(NKONF(B.s - (Nm(B,(Ni(B,(NgLINKAs ((NmOSKWAs (NmOSK(B.(NGOS(B.(NKONS(B.(NIM(B.(Np(B.(Ni(B.(N~AJKOWSKOGOs, 2006)
(NsBORNIK SODERVIT MATERIALY MEV(B.(NNAU^(B.(NKONF(B. (NSOSTOQW[IHSQ W (B2004 (NGODU W mOSKOWSKOJ I sANKT(B-(NpETERBURSKOJ KONFERENCIQH(B.s
Keywords: (NMONOGRAFIQs